Molecular characterization of the acquisition of longevity during seed maturation in soybean - Pereira Lima, Juliana Joice [UNESP]; Buitink, Julia; Lalanne, David; Rossi, Rubiana Falopa [UNESP]; Pelletier, Sandra; Amaral da Silva, Edvaldo Aparecido [UNESP]; Leprince, Olivier (Public Library Science, 2017)
Seed longevity, defined as the ability to remain alive during storage, is an important agronomic factor. Poor longevity negatively impacts seedling establishment and consequently crop yield. This is particularly problematic for soybean as seeds have a short lifespan. While the economic importance of soybean has fueled a large number of transcriptome studies during embryogenesis and seed filling, the mechanisms regulating seed longevity during late maturation remain poorly understood. Here, a detailed physiological and molecular characterization of late seed maturation was performed in soybean to obtain a comprehensive overview of the regulatory genes that are potentially involved in longevity. Longevity appeared at physiological maturity at the end of seed filling before maturation drying and progressively doubled until the seeds reached the dry state. The increase in longevity was associated with the expression of genes encoding protective chaperones such as heat shock proteins and the repression of nuclear and chloroplast genes involved in a range of chloroplast activities, including photosynthesis. An increase in the raffinose family oligosaccharides (RFO)/sucrose ratio together with changes in RFO metabolism genes was also associated with longevity. A gene co-expression network analysis revealed 27 transcription factors whose expression profiles were highly correlated with longevity. Eight of them were previously identified in the longevity network of Medicago truncatula, including homologues of ERF110, HSF6AB, NFXL1 and members of the DREB2 family. The network also contained several transcription factors associated with auxin and developmental cell fate during flowering, organ growth and differentiation. A transcriptional transition occurred concomitant with seed chlorophyll loss and detachment from the mother plant, suggesting the activation of a post-abscission program. This transition was enriched with AP2/EREBP and WRKY transcription factors and genes associated with growth, germination and post-transcriptional processes, suggesting that this program prepares the seed for the dry quiescent state and germination.